Subdural Hemorrhages in Infants: Cause and Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The incidence, cause, and clinical outcome of subdural hemorrhage in children under 2 years of age were evaluated at the Department of Child Health, Bristol, Wales, UK.